Pengaruh Kepemilikan Institusional, Leverage, dan Komite Audit Terhadap Manajemen Laba Pada Perusahaan Yang Terdaftar di PT Bursa Efek Indonesia (Studi Empiris Pada Perusahaan Yang Terdaftar Di PT Bursa Efek Indonesia Dari Tahun 2015 – 2017) - Aga Arye Perdana (LPPM - STIE SAKTI ALAM KERINCI, 2019)
This study aims to examine: 1) The effect of institutional ownership on earnings management, 2) The effect of leverage on earnings management and 3) the influence of the audit committee on earnings management. This type of research is classified into causal research. The population in this study are all companies listed on the Indonesia Stock Exchange in 2015 until 2017. The selection of samples using purposive sampling method and obtained a total sample of 194 companies. The data used in this study is secondary data. Data collection techniques with documentation techniques. The analysis used is multiple linear regression and t test to see the effect of institutional ownership, leverage and audit committee on earnings management. The test results show that: 1) institutional ownership has a significant effect on earnings management, with direction is positive at 0.640, a significance value of 0.000 is smaller than alpha 0.05 and t count> t table is equal to 19.585> 1.9645 (H1 accepted), 2) leverage has a significant effect on earnings management, with a negative direction of -0.131, a significance value of 0,000 smaller than alpha 0.05 and t count <t table that is 4.877> 1.9645 (H2 accepted) and 3) audit committee has a significant effect on earnings management, with a positive direction of 0.272, a significance value of 0,000 is smaller than alpha 0.05 and the value of t count> t table is 8,400> 1.9645 (H3 is accepted). For further research, it should use other measurement tools to detect earnings management, such as using an industrial model by Dechow, a special accrual approach model by Beaver and Engel or a real approach model of manipulation by Roychowdhury so that the results of subsequent research can provide new perspectives, both from a theoretical point of view and from the standpoint of the research results